2012
DOI: 10.1111/j.1462-2920.2012.02830.x
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of cyanobacterial diversity and community composition in mangrove soils in south‐east Brazil

Abstract: Summary Cyanobacteria act as primary producers of carbon and nitrogen in nutrient‐poor ecosystems such as mangroves. This important group of microorganisms plays a critical role in sustaining the productivity of mangrove ecosystems, but the structure and function of cyanobacteria assemblages can be perturbed by anthropogenic influences. The aim of this work was to assess the community structure and ecological drivers that influence the cyanobacterial community harboured in two Brazilian mangrove soils, and exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 54 publications
1
32
0
2
Order By: Relevance
“…The diversity of cyanobacteria has been previously explored in many environmental settings such as eutrophic lake20, soil6, phyllosphere5, hot spring249 and marine habitat50. Here we presented the first study describing the biogeographic pattern of cyanobacteria in numerous plateau lakes, a rarely explored environment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The diversity of cyanobacteria has been previously explored in many environmental settings such as eutrophic lake20, soil6, phyllosphere5, hot spring249 and marine habitat50. Here we presented the first study describing the biogeographic pattern of cyanobacteria in numerous plateau lakes, a rarely explored environment.…”
Section: Discussionmentioning
confidence: 99%
“…It indicated that the bacterial community could be strongly driven by electron acceptor availability, inducing probably different metabolic pathways52. Salinity was identified in many studies as a critical factor influencing cyanobacteria taxa256. The effects of salinity on microbial cells were related to osmoregulation and/or to metabolic changes triggered by salt, such as the ability to uptake different dissolved organic carbon compounds55.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Stal & Krumbein, ), or were placed within the genera Leptolyngbya (Nadeau et al., ), due to cryptic morphological features. Other studies have concentrated on molecular methods (Garcia‐Pichel & Belnap, ; Rigonato et al., ; Yeager et al., ), including extreme polar environments (Garcia‐Pichel, López‐Cortés, & Nübel, ), and have revealed that former culture‐based studies missed significant proportions of the microbial diversity (Torsvik & Øvreås, ; Ward, Weller, & Bateson, ). Modern approaches illustrate repeatedly the importance of combining different methodologies: Molecular data need to be correlated with ecological and morphological data, where comparisons are necessary to update or correct the present system, especially for cyanobacteria (Komárek, ).…”
Section: Introductionmentioning
confidence: 99%